Trade networks and colonial trade spillovers. Issue 4 (9th March 2017) - Berthou, Antoine; Ehrhart, Hélène
Abstract: This paper provides new empirical evidence regarding the formation of international trade networks. Established trade relations may open the gate to new trade opportunities, as they allow meeting new trade partners over time. We test this prediction and its implications for aggregate trade patterns by using the experience of ancient trade linkages between former colonies and their former colonizers (colonial trade linkages). We first show, using aggregate trade data, that former colonies have more trade with former colonizer's neighbors (colonial trade spillovers). We then show that the past export and import experience of former colonies with the colonizer have an impact on the propensity to trade similar products with third countries. In particular, the trade spillover effect is negatively related to geographical distance between third countries and the colonizer, and positively affected by their degree of economic integration.